2019
DOI: 10.1093/tbm/ibz069
|View full text |Cite
|
Sign up to set email alerts
|

What matters the adherence with BP 24-hr self-monitoring wearable device among hypertensive patients? A population-based survey

Abstract: Wearable mobile health (mHealth) technologies are a convenient and cost-effective community-based intervention to improve management of hypertension in resource-limited populations. This study was designed to evaluate user characteristics of blood pressure (BP) wearable technology among a community-based population in a rural area of China. During the period of April through July 2018, a self-monitoring intervention program for hypertension control was implemented in a remote area of central China. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Hypertensive elderly living in rural mountain areas are a vulnerable group in China. Moreover, the one‐child policy and internal migration from rural to urban areas have greatly increased “empty‐nested elders” (Zhang, Tan, et al, 2019; Zhang, Xu, et al, 2019; Zhang, Yang, et al, 2019). Thus, it is of high implication to study their adherence to wearable BP monitor device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertensive elderly living in rural mountain areas are a vulnerable group in China. Moreover, the one‐child policy and internal migration from rural to urban areas have greatly increased “empty‐nested elders” (Zhang, Tan, et al, 2019; Zhang, Xu, et al, 2019; Zhang, Yang, et al, 2019). Thus, it is of high implication to study their adherence to wearable BP monitor device.…”
Section: Resultsmentioning
confidence: 99%
“…Upon receipt of the ambulatory BP monitor, participants were trained on the usage of the wristband and provided with a written instruction manual. More details of the research process were reported elsewhere (Zhang, Tan, Si, & Huang, 2019; Zhang, Xu, et al, 2019; Zhang, Yang, et al, 2019). Each community had a “super user,” a participant volunteer who helped community participants with hub issues and communicated with investigators.…”
Section: Methodsmentioning
confidence: 99%
“…The Self-Monitoring Intervention Programme for Hypertension Control was a randomized trial conducted among 6 primary care centers within a remote mountainous districts of Hubei province, China. Details of the Program's study design and organizations have been published elsewhere (20).…”
Section: Methodsmentioning
confidence: 99%
“…Health education about hypertension aims to make the elderly and families understand the process of hypertension, signs, and hypertension symptoms (25,26). The early stages require an assessment of disease, self-efficacy, self-management behavior.…”
Section: Knowledge About Diseasementioning
confidence: 99%
“…Blood pressure monitoring in the elderly with hypertension includes monitoring blood pressure, performing proper procedures to measure blood pressure, checking the calibration of a blood pressure meter if you have one at home, maintaining blood pressure targets, using a diary to monitor blood pressure from time to time, and contacting health services (25). Blood pressure monitoring aims to monitor blood pressure conditions so that it can prevent uncontrolled hypertension.…”
Section: Blood Pressure Controlmentioning
confidence: 99%